2008
DOI: 10.1016/j.jpainsymman.2007.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Palliative Sedation: A Review of the Research Literature

Abstract: The overall aim of this paper is to systematically review the following important aspects of palliative sedation: prevalence, indications, survival, medication, food and fluid intake, decision making, attitudes of physicians, family experiences, and efficacy and safety. A thorough search of different databases was conducted for pertinent research articles published from 1966 to June 2007. The following keywords were used: end of life, sedation, terminal sedation, palliative sedation, refractory symptoms, and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
163
1
35

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 220 publications
(209 citation statements)
references
References 53 publications
10
163
1
35
Order By: Relevance
“…However, in case of refractory symptoms leading to 20 unbearable suffering such as intolerable pain, dyspnea, and delir- 21 ium, a more drastic option may be chosen, known as palliative 22 sedation (Table 1). In these cases, comfort is sought by reducing 23 the patient's level of consciousness [12,23]. Although palliative 24 sedation is ethically controversial and some studies have ques- 25 tioned its efficacy and safety [29], this practice has substantially in- 26 creased.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, in case of refractory symptoms leading to 20 unbearable suffering such as intolerable pain, dyspnea, and delir- 21 ium, a more drastic option may be chosen, known as palliative 22 sedation (Table 1). In these cases, comfort is sought by reducing 23 the patient's level of consciousness [12,23]. Although palliative 24 sedation is ethically controversial and some studies have ques- 25 tioned its efficacy and safety [29], this practice has substantially in- 26 creased.…”
mentioning
confidence: 99%
“…Paradoxically, the inability to report distress might also be 159 aggravated or even blocked by the use of drugs that might abolish 160 potential further communication and even facial expressions [9]. Palliative sedation is normal medical practice and must be clearly distinguished from the termination of life [35] Proportionality: the degree of sedation must not be deeper than necessary to relieve suffering [11,12,23,35] Palliative sedation will not (usually) hasten death (and that is certainly not the intention) [ [24] o ''Monitoring (observational) scales exist but the usefulness of these scales has not been proven'' [16] o ''Presently no particular scale can be recommended'' [16,24] ''Scales involving administration of painful stimuli are not acceptable'' [16] Frequency of monitoring: every 20 minutes until adequate sedation has been reached and then at least once a day [15,16] Nurses have the explicit task to observe, measure, and report [24] 161 Hence, some patients might have subjective phenomenological …”
mentioning
confidence: 99%
“…4 Several studies have reported use of PS for fatigue and malaise 6,16 ; however, whether these symptoms represent existential or physical suffering is debatable. A few studies have directly addressed the use of PS for existential or psychological suffering.…”
Section: Non-physical Sufferingmentioning
confidence: 99%
“…During the late 1990s, several important court cases in the United States brought the issue of PS to the forefront and clarified the legality of the right to palliation at end of life. 2,3 Studies have shown that PS is effective, with efficacy rates ranging from 71% to 92%, 4 usually defined as the patient, family, or physician's perceived relief of refractory physical symptoms. In many settings, PS is uncommon, although a recent review revealed considerable variability in the prevalence of PS in the United States and other countries.…”
mentioning
confidence: 99%
See 1 more Smart Citation